Nepravdni in izvršilni postopki v ustavnosodni presoji - Jadek-Pensa, Dunja (Podjetje in delo, 2018)
This article is composed of two parts. The first part briefly outlines the importance of a fair trial for implementing the rule of law and supporting the confidence in judiciary. The second part summarises some of the decisions of the Constitutional Court concerning certain dilemmas of enforcment and non-litigious civil proceedings. The idea is to present a constiutional dimension of these dilemmas and basic characteristics of the rule-governed decision-making when a constitutional issue is raised.
Keywords: izvržba zaradi zagotovitve stikov z otroki; načelo pravne države; obrazložena sodna odločba; odvzem svobode; poštenost postopka; ustavno sodišče; začasni zastopnik pri izvršbi na stanovanje; zloraba izvržbe